Nicotine Dependence and Incident Hip Replacement Surgery in Individuals with Type 2 Diabetes Mellitus, TRINET-X, 2021 - Wiener, R. Constance; Gaydos, Melissa Suann; Cochran, Jill; Morgan, Susan (The Journal of Hip Surgery, 2022)
The purpose of this research is to examine the association between nicotine dependence (yes, no) and hip replacement (yes, no) among people with type 2 diabetes mellitus (T2DM). Data were obtained through the TRINET-X data depository of 18 years or older patients with T2DM and nicotine dependence history. Then, the incidence of hip replacement surgery was determined. Propensity score matching (PSM) was used to determine the risk of hip replacement surgery. After PSM, the risk ratio of hip replacement surgery among people with T2DM was 1.45 (95% confidence interval: 1.45, 1.57; p < 0.0001) for those who had nicotine dependence versus those who did not. Nicotine dependence among people with T2DM was identified as a risk factor for future hip replacement need. Patients who have nicotine dependence should be cautioned about this potential risk.
Keywords: hip replacement; type 2 diabetes mellitus; nicotine dependence